Dinamika Ekspresi Religius Subkultur: Sebuah Perlawan Terhadap Normativitas Beragama di Media Sosial - Rahmah, Hilda; Harlen Tapotubun, Hanry (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
This article aims to analyze at the dynamics of millennial's religious expressions in real life and on social media. Using a qualitative approach with netnographic methods and literature studies, this study compares the virtual data through interviews and participant observation on the Instagram and WhatsApp. Based on the findings, millennial's religious expressions on social media tend to be dynamic, different from their daily reality which tends to follow the dominant style of religious expression in society. Woodward calls it fluid, that identity can continue to change following the social setting in which the individual is located. This dualism cannot be separated from the existence of a dominant culture that requires millennials to express their religiosity in activities such as diligently worshiping, being members of religious organizations, and participating in spiritual activities. These activities are considered as an established religious expression in society, and even becomes a standard in determining a person's level of religiosity as well as the way to exclude someone from the community in which he or she lives. The phenomenon of millennial religious expression as opposed to the dominant religious culture can be identified as part of a subculture. Subcultural groups often voice their aspirations in various forms, including ways to go against the dominant and popular social norms in a society. However, their fluid character and identity shows that the form of resistance is not always shown by a fierce resistance in one space, in this case in a virtual space. The culture of religious expression on social media that contrasts with expressions in real life places millennials in a post-subculture position, where this indicates that there are negotiations to convey an aspiration.